Analisis Pengelolaan Penjualan Energi Listrik Pascabayar dan Prabayar pada B’right PLN Batam - Ely Kartikaningdyah; Vivi Octaviani (Politeknik Negeri Batam, 2014)
This study discusses Electrical Energy sales made B'right PLN Batam include electric energy sales of prepaid and postpaid. This study aims to determine how it compares to the management of electrical energy sales prepaid and postpaid, how recognition and recording of electric energy sales of prepaid and postpaid, and whether the admission and records B'right PLN Batam is in accordance with SFAS No. 23. This study used a descriptive analysis , The collection of data obtained through interviews and documentation prepared and processed in order to obtain an overview of cash sales and credit sales. The authors draw the conclusion that the sales made B'right PLN Batam for the sale of prepaid electric energy using the cash basis method while sales of electrical energy postpaid accrual basis method. Recognition and records maintained by B'right PLN Batam is in conformity with the theory and PSAK No. 23